Analysis and detection method for formula content of negative electrode material and application

Through the method of thermogravimetric analysis combined with standard substance testing, the problem of lack of system negative electrode material formulation content analysis and detection in the prior art is solved, and the accurate detection of the content of water-based binder and aqueous dispersant in lithium-ion batteries is achieved, thereby improving the accuracy of battery performance and failure analysis.

CN119845776AActive Publication Date: 2025-04-18XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510029558.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-18
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The prior art lacks a systematic method for the negative electrode material formulation content analysis and detection, and it is difficult to accurately detect the content of water-based binders and aqueous dispersants of the negative electrode material in lithium-ion batteries.

Method used

Through thermogravimetric analysis (TG test) combined with aqueous dispersant and aqueous binder standard substance test, the influence of weight loss of carbon materials is eliminated, and the content of aqueous binder and aqueous dispersant in the negative electrode material is accurately calculated.

Benefits of technology

High reliability and accuracy detection of the content of water-based binder and aqueous dispersant in the negative electrode material is achieved, and the accuracy of lithium-ion battery performance characterization and failure analysis is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119845776A_ABST
    Figure CN119845776A_ABST
Patent Text Reader

Abstract

The invention discloses an analysis and detection method and application of the formula content of a negative electrode material, and the analysis and detection method comprises the following steps: taking part of the negative electrode material, and carrying out first thermogravimetric analysis to obtain a first weight loss ratio; removing the water-based dispersing agent from the residual negative electrode material to obtain a negative electrode material without the water-based dispersing agent; performing second thermogravimetric analysis on the negative electrode material without the aqueous dispersant to obtain a second weight loss ratio; respectively carrying out third thermogravimetric analysis and fourth thermogravimetric analysis on respective standard substances of the aqueous binder and the aqueous dispersant to obtain a third weight loss ratio and a fourth weight loss ratio; the product of the ratio of the second weight loss ratio to the third weight loss ratio and 100% is used as the mass content of the aqueous binder in the negative electrode material. According to the analysis and detection method for the formula content of the negative electrode material, the removal effect of the aqueous dispersant can be detected through the TG curve, and the reliability and the accuracy of the analysis and detection result of the content of the binder and the like are high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to an analysis and detection method for the content of a negative electrode material formula and its application. Background Art

[0002] The content of main materials, binders, dispersants and conductive agents in the negative electrode formula of lithium-ion batteries is one of the core technologies of lithium-ion batteries. Different formula contents correspond to different performances and also correspond to different failure manifestations. Establishing a method for analyzing and detecting the content of lithium-ion battery negative electrode formula is of great significance to the failure analysis and performance characterization of lithium-ion batteries.

[0003] At present, in the field of lithium-ion batteries, the relevant technology detects the uniformity of SBR distribution in the electrode through bromine water treatment and re-extraction, but there is no systematic method for analyzing and detecting the content of the negative electrode formula.

[0004] Therefore, there is an urgent need for a systematic method for analyzing and detecting the content of the negative electrode formula. Summary of the invention

[0005] In view of this, one purpose of the present application is to provide an analytical detection method for the content of the negative electrode material formula, by eliminating the influence of the weight loss of the carbon material, first performing a TG test on the entire negative electrode material of the graphite negative electrode, and then removing the aqueous dispersant and performing the TG test again, combining the weight loss rate of each TG test and the weight loss rate obtained by the TG test of the aqueous binder and aqueous dispersant standard substance, the content of the aqueous binder and aqueous dispersant in the negative electrode material can be accurately calculated. This method can verify the removal effect of the aqueous dispersant through the TG curve, and the analytical detection results of the content of the aqueous binder and aqueous dispersant are highly reliable and accurate.

[0006] Another object of the present application is to provide an application of a method for analyzing and detecting the content of a negative electrode material formula.

[0007] To achieve the above-mentioned purpose, the first aspect of the present application proposes a method for analyzing and detecting the content of a negative electrode material formula, wherein the negative electrode material is composed of a carbon material, an aqueous binder and an aqueous dispersant, and the carbon material is composed of graphite and a carbon-based conductive agent; the method for analyzing and detecting comprises:

[0008] Taking a portion of the negative electrode material for a first thermogravimetric analysis to obtain a first weight loss rate;

[0009] removing the aqueous dispersant from the remaining negative electrode material to obtain a negative electrode material free of the aqueous dispersant;

[0010] Performing a second thermogravimetric analysis on the negative electrode material not containing the aqueous dispersant to obtain a second weight loss rate;

[0011] The standard substances of the water-based binder and the water-based dispersant are subjected to a third thermogravimetric analysis and a fourth thermogravimetric analysis within the first temperature range to obtain a third weight loss rate and a fourth weight loss rate; within the first temperature range, the graphite does not undergo thermal weight loss, and the weight loss of the carbon-based conductive agent is negligible;

[0012] The mass content of the aqueous binder in the negative electrode material is calculated according to formula (1), and the mass content of the aqueous dispersant in the negative electrode material is calculated according to formula (2):

[0013] C1=D2 / D1*100% Formula (1)

[0014] C2=(D4-D2) / D3*100% Formula (2)

[0015] Among them, D1 is the third weight loss rate, D2 is the second weight loss rate, D3 is the fourth weight loss rate, D4 ​​is the first weight loss rate, C1 is the mass content of the aqueous binder in the negative electrode material, and C2 is the mass content of the aqueous dispersant in the negative electrode material.

[0016] In some embodiments, the method for analyzing and detecting the content of the negative electrode material formula further includes:

[0017] The mass content of the carbon material in the negative electrode material is calculated according to the following formula:

[0018] C3=(1-C1-C2)*100%

[0019] Wherein, C3 is the mass content of the carbon material in the negative electrode material.

[0020] In some embodiments, the first temperature ranges from 25-750°C.

[0021] In some embodiments, the third thermogravimetric analysis and the fourth thermogravimetric analysis are both performed in an inert gas atmosphere.

[0022] In some embodiments, the heating rates of the third thermogravimetric analysis and the fourth thermogravimetric analysis are both 1-3 k / min.

[0023] In some embodiments, the conditions of the first thermogravimetric analysis and the second thermogravimetric analysis are: inert gas atmosphere, heating rate 1-3k / min, and test temperature range 25-750°C.

[0024] In some embodiments, removing the aqueous dispersant from the remaining negative electrode material to obtain a negative electrode material free of the aqueous dispersant comprises:

[0025] The remaining negative electrode material is subjected to a first reflux in a first solvent, followed by a first filtration and a first drying to obtain the negative electrode material free of the aqueous dispersant.

[0026] In some embodiments, the first solvent includes water and an organic solvent, and the organic solvent includes at least one of methanol, ethanol, ethylene glycol, and propanol.

[0027] In some embodiments, the temperature of the first reflux is 60-90°C.

[0028] In some embodiments, the first reflux time is 4-6 hours.

[0029] In some embodiments, the method for analyzing and detecting the negative electrode material formula content further includes a step of first grinding the negative electrode material before performing the first thermogravimetric analysis and the step of removing the aqueous dispersant.

[0030] In some embodiments, the method for analyzing and detecting the negative electrode material formula content further includes a step of performing a second grinding on the negative electrode material that does not contain the aqueous dispersant before performing the second thermogravimetric analysis.

[0031] In some embodiments, the negative electrode material is a fresh negative electrode material mixed with a carbon material, an aqueous binder and an aqueous dispersant, or is a negative electrode material obtained from a negative electrode sheet of a lithium-ion battery to be tested.

[0032] In some embodiments, when the negative electrode material is a negative electrode material obtained from a negative electrode sheet of a lithium ion battery to be tested, the method for analyzing and detecting the negative electrode material formula content further includes:

[0033] The negative electrode plate is washed, dried for a second time, and then the negative electrode material layer of the negative electrode plate is scraped off. Subsequently, a second reflow, a second filtration, and a third drying are performed in a second solvent to obtain the negative electrode material.

[0034] In some embodiments, the washing solvent and the second solvent both include at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methanol, ethanol, ethylene glycol, and propanol.

[0035] In some embodiments, the temperature of the second reflux is 60-90°C.

[0036] In some embodiments, the second reflux time is 4-6 hours.

[0037] In some embodiments, when the negative electrode material is a negative electrode material obtained from a negative electrode sheet of a lithium ion battery to be tested, the method for analyzing and detecting the negative electrode material formula content further includes:

[0038] The lithium-ion battery to be tested is discharged to a cut-off voltage, and then disassembled in an environment with a humidity of less than 10% to obtain the negative electrode sheet.

[0039] In some embodiments, the discharge current of the lithium ion battery to be tested is 0.01-0.05C.

[0040] In some embodiments, the graphite includes at least one of artificial graphite, natural graphite, and mesophase carbon microbeads.

[0041] In some embodiments, the carbon-based conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, porous carbon, graphene, multi-walled carbon nanotubes, and single-walled carbon nanotubes.

[0042] In some embodiments, the water-based binder includes at least one of styrene butadiene and modified organic emulsions thereof, styrene acrylate and modified organic emulsions thereof, polyethylene emulsion, and polypropylene emulsion.

[0043] In some embodiments, the aqueous dispersant includes at least one of carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxyethyl cellulose, and lithium carboxyethyl cellulose.

[0044] The second aspect of the present application relates to the application of the analysis and detection method of the negative electrode material formula content described in the present application in the field of secondary batteries.

[0045] The analysis and detection method of the negative electrode material formula content described in this application can at least bring the following beneficial effects:

[0046] By eliminating the influence of carbon material weight loss, the entire graphite negative electrode material is first subjected to TG test, and then the TG test is performed again after removing the aqueous dispersant. The weight loss rate of each TG test and the weight loss rate obtained by TG test of aqueous binder and aqueous dispersant standard substances can be combined to accurately calculate the content of aqueous binder and aqueous dispersant in the negative electrode material. This method can verify the removal effect of aqueous dispersant through TG curve, and the analysis and detection results of the content of aqueous binder and aqueous dispersant are highly reliable and accurate.

[0047] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings.

[0049] in:

[0050] Figure 1 This is a flow chart of a method for analyzing and detecting the content of a negative electrode material formula, shown as an exemplary embodiment of the present application.

[0051] Figure 2 It is the weight loss curve (TG-DTG curve) of the negative electrode material (solid 1) in Example 1.

[0052] Figure 3 This is the weight loss curve (TG-DTG curve) of the negative electrode material from which CMC is removed in Example 1.

[0053] Figure 4 This is the weight loss curve (TG-DTG curve) of the artificial graphite and carbon-based conductive agent SP standard substance in Example 1.

[0054] Figure 5 This is the weight loss curve (TG-DTG curve) of the water-based binder SBR and water-based dispersant CMC standard substances in Example 1. DETAILED DESCRIPTION

[0055] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.

[0056] In this application, the disclosure of numerical ranges includes all values ​​within the entire range and the disclosure of further subdivided ranges, including the endpoints and sub-ranges given in these ranges.

[0057] In this application, the raw materials, equipment, etc. involved, unless otherwise specified, are all raw materials and equipment that can be made through commercial channels or known methods; the methods involved, unless otherwise specified, are all conventional methods.

[0058] The term "and / or", when used in a list of two or more items, means that any of the listed items can be used alone or in combination with any one or more of the listed items. For example, the expression "A and / or B" is intended to mean A or B or A and B, that is, only A, only B, or a combination of A and B.

[0059] The inventors found that by selecting a suitable atmosphere, the weight loss effect of carbon materials (graphite and carbon-based conductive agents) can be eliminated within a special temperature range. In an inert gas atmosphere such as N2, graphite and carbon-based conductive agents do not lose weight or lose weight so little that it can be ignored at 25-750°C. The weight loss peaks of aqueous binders such as SBR and aqueous dispersants such as CMC at 25-750°C are split more completely. Therefore, the aqueous dispersant or aqueous binder in the negative electrode material can be first removed (for example, by selecting a suitable solvent for dissolution and removal), and the removal effect of the aqueous dispersant can be verified by the TG curve. Then, the content of aqueous binders such as SBR and aqueous dispersants such as CMC in the negative electrode material can be calculated by combining the thermal weight loss ratio of standard substances such as aqueous dispersants such as CMC and aqueous binders such as SBR. Then, based on the sum of the components in the negative electrode material being 100% (that is, 1), the content of carbon materials (graphite and carbon-based conductive agents) in the negative electrode material can be calculated.

[0060] Specifically, when the negative electrode material is obtained from the negative electrode plate of the lithium ion battery to be tested, the negative electrode material mixed powder is washed to remove the influence of impurities on subsequent analysis, and the washed negative electrode material powder is subjected to a TG test to obtain the weight loss ratio (i.e., the first weight loss ratio) of the aqueous binder, the aqueous dispersant and the carbon material (graphite and carbon-based conductive agent); the aqueous dispersant is then dissolved, and a TG test is performed on a mixture containing only aqueous binders and carbon materials (graphite and carbon-based conductive agents), and the content of aqueous binders such as SBR is calculated according to the weight loss ratio of pure substances of aqueous binders such as SBR (i.e., the third weight loss ratio) and the weight loss ratio of the negative electrode material after removing the aqueous dispersant (i.e., the second weight loss ratio); the proportion of aqueous binders such as SBR is then brought into the first weight loss ratio, and the proportion of aqueous dispersants is calculated according to the weight loss ratio of pure substances of aqueous dispersants (i.e., the fourth weight loss ratio), and the content of carbon materials (graphite and carbon-based conductive agents) in the graphite negative electrode of the lithium ion battery is obtained by calculation. It has been verified that the analytical detection method for the negative electrode material formula content of the embodiment of the present application has high reliability and accuracy for the detection of the content of the aqueous binder and the aqueous dispersant.

[0061] The following describes in detail a method for analyzing and detecting the content of a negative electrode material formula according to an embodiment of the present application with reference to the accompanying drawings.

[0062] Figure 1 This is a flow chart of a method for analyzing and detecting the content of a negative electrode material formula, shown as an exemplary embodiment of the present application.

[0063] like Figure 1 As shown, the analysis and detection method of the negative electrode material formula content includes the following steps:

[0064] S101, taking a portion of the negative electrode material to perform a first thermogravimetric analysis to obtain a first weight loss rate.

[0065] In the embodiments of the present application, the first weight loss rate is also the weight loss rate of the negative electrode material.

[0066] In some embodiments, the negative electrode material consists of a carbon material, an aqueous binder and an aqueous dispersant, and the carbon material consists of graphite and a carbon-based conductive agent.

[0067] In some embodiments, the graphite includes but is not limited to at least one of carbon-based negative electrode active materials such as artificial graphite, natural graphite, and mesophase carbon microbeads.

[0068] In some embodiments, the carbon-based conductive agent includes but is not limited to at least one of conductive carbon black, acetylene black, Ketjen black, porous carbon, graphene, multi-walled carbon nanotubes, single-walled carbon nanotubes and the like in chain-shaped, granular, porous or tubular form.

[0069] In some embodiments, the water-based binder includes, but is not limited to, at least one of styrene butadiene and its modified organic emulsion (SBR), styrene acrylate and its modified organic emulsion, polyethylene emulsion, and polypropylene emulsion.

[0070] In some embodiments, the aqueous dispersant includes at least one of carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxyethyl cellulose, and lithium carboxyethyl cellulose.

[0071] In the embodiments of the present application, a small amount of the negative electrode material can be used for the first thermogravimetric analysis (TG test), for example, 5-10 mg.

[0072] In some embodiments, the test conditions of the first thermogravimetric analysis are: inert gas atmosphere, heating rate 1-3k / min, and test temperature range 25-750°C.

[0073] Exemplarily, the inert gas includes at least one of nitrogen (N2), helium or argon, etc., and nitrogen can be selected.

[0074] For example, in the first thermogravimetric analysis, the heating rate includes but is not limited to 1 k / min, 2 k / min or 3 k / min.

[0075] In some embodiments, the negative electrode material is a fresh negative electrode material mixed with a carbon material, an aqueous binder and an aqueous dispersant.

[0076] In other embodiments, the negative electrode material is a negative electrode material obtained from a negative electrode sheet of a lithium-ion battery to be tested.

[0077] It is understood that in the embodiments of the present application, the lithium-ion battery to be tested refers to a lithium-ion battery using graphite as the negative electrode active material (i.e., negative electrode active material), including lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium titanate as the positive electrode active material and graphite as the negative electrode active material. The negative electrode plate refers to a negative electrode plate using graphite as the negative electrode active material, and its negative electrode material is the negative electrode material described in the present application.

[0078] In some embodiments, when the negative electrode material is a negative electrode material obtained from a negative electrode sheet of a lithium ion battery to be tested, the method for analyzing and detecting the negative electrode material formula content further includes:

[0079] The negative electrode plate is washed, dried for a second time, and then the negative electrode material layer of the negative electrode plate is scraped off. Subsequently, a second reflow, a second filtration, and a third drying are performed in a second solvent to obtain the negative electrode material.

[0080] In some embodiments, the washing method comprises the following steps:

[0081] (1) placing the negative electrode sheet into a washing solvent, leaving it to stand for a period of time, and then using ultrasound to clean the negative electrode sheet;

[0082] (2) The negative electrode sheet after ultrasonic cleaning is rinsed on the front and back sides of the negative electrode sheet using a spray bottle filled with a washing solvent.

[0083] In the embodiments of the present application, the purpose of washing the negative electrode sheet is to remove byproducts on the surface of the negative electrode sheet.

[0084] In some embodiments, the washing solvent and the second solvent include but are not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methanol, ethanol, ethylene glycol, propanol, and the like.

[0085] In some embodiments, the second drying method includes but is not limited to at least one of drying (eg, drying in a forced air drying oven, etc.), vacuum drying, spray drying, etc.

[0086] In the embodiment of the present application, the purpose of the second reflux is to remove lithium salts and further remove byproducts on the surface of the negative electrode. Therefore, the second solvents mentioned above are all solvents that can dissolve and remove lithium salts and other impurities not composed of the negative electrode material, and the reflux method is more thorough in removing lithium salts and impurities.

[0087] Therefore, the washing solvent and the second solvent are solvents that can dissolve the lithium salt and the byproducts on the surface of the negative electrode plate, but cannot dissolve the negative electrode material composition.

[0088] In some embodiments, the second reflux temperature is 60-90°C, including but not limited to 65°C, 70°C, 75°C, 80°C or 85°C.

[0089] In some embodiments, the second reflux time is 4-6 hours, including but not limited to 4.5 hours, 5 hours or 6 hours.

[0090] In some embodiments, when the negative electrode material is a negative electrode material obtained from a negative electrode sheet of a lithium ion battery to be tested, the method for analyzing and detecting the negative electrode material formula content further includes:

[0091] The lithium-ion battery to be tested is discharged to a cut-off voltage, and then disassembled in an environment with a humidity of less than 10% to obtain the negative electrode sheet.

[0092] In some embodiments, the discharge current of the lithium ion battery to be tested is 0.01-0.05C.

[0093] S102, removing the aqueous dispersant from the remaining negative electrode material to obtain a negative electrode material that does not contain the aqueous dispersant.

[0094] In the embodiments of the present application, the method of removing the aqueous dispersant from the remaining negative electrode material includes but is not limited to at least one of reflux and the like.

[0095] As an optional example, removing the aqueous dispersant from the remaining negative electrode material to obtain a negative electrode material without the aqueous dispersant comprises:

[0096] The remaining negative electrode material is subjected to a first reflux in a first solvent, followed by a first filtration and a first drying to obtain the negative electrode material free of the aqueous dispersant.

[0097] In the embodiment of the present application, the first solvent is a solvent that can dissolve the aqueous dispersant but does not dissolve the aqueous binder and the carbon material (graphite and carbon conductive agent). That is, the first solvent is a solvent that only dissolves the aqueous dispersant in the negative electrode material.

[0098] In some embodiments, the first solvent includes water and an organic solvent.

[0099] Exemplarily, the organic solvent includes but is not limited to at least one of methanol, ethanol, ethylene glycol, propanol, and the like.

[0100] Exemplarily, the mass ratio of water to organic solvent in the first organic solvent is (30-70):(70-30), including but not limited to 30:70, 40:60, 50:50 or 60:40, etc.

[0101] As an optional example, the first organic solvent is water and an organic solvent.

[0102] In some embodiments, the temperature of the first reflux is 60-90°C, including but not limited to 65°C, 70°C, 75°C, 80°C or 85°C.

[0103] In some embodiments, the first reflux time is 4-6 hours, including but not limited to 4.5 hours, 5 hours or 6 hours.

[0104] In some embodiments, the first drying method includes but is not limited to at least one of drying (eg, drying in a forced air drying oven, etc.), vacuum drying, spray drying, etc.

[0105] S103, performing a second thermogravimetric analysis on the negative electrode material not containing the aqueous dispersant to obtain a second weight loss rate D2.

[0106] In some embodiments, the test conditions of the second thermogravimetric analysis (TG test) are: inert gas atmosphere, heating rate 1-3 k / min, and test temperature range 25-750°C.

[0107] Exemplarily, the inert gas includes at least one of nitrogen (N2), helium or argon, etc., and nitrogen can be selected.

[0108] Exemplarily, in the second thermogravimetric analysis, the heating rate includes but is not limited to 1 k / min, 2 k / min or 3 k / min, etc.

[0109] In the embodiments of the present application, the second weight loss rate is also the weight loss rate of the negative electrode material without the aqueous dispersant.

[0110] S104. Perform a third thermogravimetric analysis and a fourth thermogravimetric analysis on the standard substances of the water-based binder and the water-based dispersant within the first temperature range, respectively, to obtain a third weight loss rate and a fourth weight loss rate; within the first temperature range, the graphite does not undergo thermal weight loss, and the weight loss of the carbon-based conductive agent is negligible.

[0111] In the embodiments of the present application, the third weight loss rate is also the weight loss rate of the water-based binder standard substance, and the fourth weight loss rate is also the weight loss rate of the water-based dispersant standard substance.

[0112] In some embodiments, the first temperature ranges from 25-750°C.

[0113] In some embodiments, the third thermogravimetric analysis (TG test) and the fourth thermogravimetric analysis (TG test) are both performed in an inert gas atmosphere.

[0114] Exemplarily, the inert gas includes at least one of nitrogen (N2), helium or argon, etc., and nitrogen can be selected.

[0115] In some embodiments, the heating rates of the third thermogravimetric analysis and the fourth thermogravimetric analysis are both 1-3 k / min, including but not limited to 1 k / min, 2 k / min or 3 k / min.

[0116] It should be noted that in the embodiments of the present application, the TG test shows that graphite has no weight loss at 25-750°C under an inert atmosphere, and carbon-based conductive agents such as SP have a weight loss of less than 0.4% at 25-750°C under an inert atmosphere. It is well known in the art that in the formulation of negative electrode materials with graphite as the negative electrode active material, the proportion of carbon-based conductive agents such as SP is generally less than 3wt%, and the weight loss of carbon-based conductive agents such as SP in the entire negative electrode material is less than 0.02%, which can be ignored. The first solvent only dissolves aqueous dispersants such as CMC, but does not dissolve aqueous binders such as SBR, and therefore has no effect on the SBR content.

[0117] S105. Calculate the mass content of the aqueous binder in the negative electrode material according to formula (1), and calculate the mass content of the aqueous dispersant in the negative electrode material according to formula (2):

[0118] C1=D2 / D1*100% Formula (1)

[0119] C2=(D4-D2) / D3*100% Formula (2)

[0120] Among them, D1 is the third weight loss rate, D2 is the second weight loss rate, D3 is the fourth weight loss rate, D4 ​​is the first weight loss rate, C1 is the mass content of the aqueous binder in the negative electrode material, and C2 is the mass content of the aqueous dispersant in the negative electrode material.

[0121] It can be understood that step S105 can also be expressed as: the product of the ratio of the second weight loss rate to the third weight loss rate and 100% is used as the mass content of the aqueous binder in the negative electrode material, and the product of the difference between the first weight loss rate and the second weight loss rate and the ratio of the fourth weight loss rate and 100% is used as the mass content of the aqueous dispersant in the negative electrode material.

[0122] In some embodiments, the method for analyzing and detecting the content of the negative electrode material formula further includes:

[0123] The mass content of the carbon material in the negative electrode material is calculated according to the following formula (3):

[0124] C3=(1-C1-C2)*100% Formula (3)

[0125] Wherein, C3 is the mass content of the carbon material in the negative electrode material.

[0126] In some embodiments, the method for analyzing and detecting the negative electrode material formula content further includes a step of first grinding the negative electrode material before performing the first thermogravimetric analysis and the step of removing the aqueous dispersant.

[0127] In some embodiments, the method for analyzing and detecting the negative electrode material formula content further includes a step of performing a second grinding on the negative electrode material that does not contain the aqueous dispersant before performing the second thermogravimetric analysis.

[0128] The analysis and detection method of the negative electrode material formula content of the embodiment of the present application, by eliminating the influence of the weight loss of the carbon material, first performs a TG test on the entire negative electrode material of the graphite negative electrode, and then removes the aqueous dispersant and performs a TG test again, combining the weight loss rate of each TG test and the weight loss rate obtained by the TG test of the aqueous binder and aqueous dispersant standard substance, the content of the aqueous binder and aqueous dispersant in the negative electrode material can be accurately calculated. This method can verify the removal effect of the aqueous dispersant through the TG curve, and the analytical detection results of the content of the aqueous binder and aqueous dispersant are highly reliable and accurate.

[0129] The analysis and detection method of the negative electrode material formula content of the embodiment of the present application can be widely used in the field of secondary batteries.

[0130] Certain features of the present technology are further illustrated in the following non-limiting examples.

[0131] In the following embodiments, the mass content of the aqueous binder in the negative electrode material is denoted by C1, the mass content of the aqueous dispersant in the negative electrode material is denoted by C2, and the mass content of the carbon material (artificial graphite and carbon-based conductive agent) in the negative electrode material is denoted by C3; the weight loss rate of solid 1 (i.e., the negative electrode material), i.e., the first weight loss rate, is denoted by D4; the weight loss rate of solid 2 (i.e., the negative electrode material not containing the aqueous dispersant or the negative electrode material with the aqueous dispersant removed), i.e., the second weight loss rate, is denoted by D2; the weight loss rate of the aqueous binder standard substance, i.e., the third weight loss rate, is denoted by D1; the weight loss rate of the aqueous dispersant standard substance, i.e., the fourth weight loss rate, is denoted by D3.

[0132] Then the mass content C1 of the aqueous binder, the mass content C2 of the aqueous dispersant and the mass content C3 of the carbon material (artificial graphite and carbon-based conductive agent) in the negative electrode material are calculated according to formula (1), formula (2) and formula (3), respectively:

[0133] C1=D2 / D1*100% Formula (1)

[0134] C2=(D4-C1*D1) / D3*100%=(D4-D2) / D3*100% Formula (2)

[0135] C3=(1-C1-C2)*100% Formula (3)

[0136] Example 1

[0137] It is known that the formula of a negative electrode material for a lithium ion battery using graphite as a negative electrode active material is: artificial graphite: aqueous dispersant CMC: aqueous binder SBR: carbon-based conductive agent SP = 95.6wt%: 1.4wt%: 2wt%: 1wt%.

[0138] The inventors, on the premise that the material composition of the negative electrode material is known but the specific content of each material composition is unknown, use the analysis and detection method of the negative electrode material formula content of this embodiment to analyze and detect the mass content of the aqueous binder SBR, the aqueous dispersant CMC and the carbon material (artificial graphite and the carbon-based conductive agent SP) in the negative electrode material. The specific analysis and detection method includes the following steps:

[0139] S1, take the above-mentioned lithium-ion battery to be tested that uses graphite as the negative electrode active material, discharge it at 0.02C to a cut-off voltage of 2.0V, disassemble the battery in an environment with a humidity of less than 10% (for example, an environment with a humidity of 5%), and obtain 30g of the negative electrode plate; completely immerse the obtained negative electrode plate in dimethyl carbonate (DMC), let it stand for 3h, and then use ultrasound to clean the negative electrode plate for 3min; after ultrasonic cleaning of the negative electrode plate, immediately take out the negative electrode plate from DMC and rinse the front and back of the negative electrode plate with a spray bottle containing DMC; put the rinsed negative electrode plate into a blast drying oven for drying.

[0140] S2. Take the baked negative electrode sheet, place it flat on a glass plate, use a ceramic knife to scrape 5 g of negative electrode material layer powder, put the scraped negative electrode material layer powder into a conical flask, add 100 mL of anhydrous ethanol to a clean conical flask, place the conical flask on a heating table, connect the reflux tube and condensed water, and reflux for 5 hours at 80°C.

[0141] S3, use filtration to separate the mixed solution in the conical flask that has completed the reflux in step S2, put the solid 1 (i.e., the negative electrode material) obtained by centrifugation into a surface dish with a cover, and place it in a forced air drying oven to dry; take the dried solid 1 and put it into an agate mortar to grind it into powder, and take 10 mg of the ground solid 1 powder for TG testing. The TG test conditions are: N2 atmosphere, heating rate 2k / min, test temperature range 25-750℃. The weight loss curve of solid 1 (i.e., negative electrode material) obtained by TG test is as follows Figure 2As shown, according to the weight loss curve, the weight loss rate of solid 1 (ie, negative electrode material) is obtained, that is, the first weight loss rate, recorded as D4, and the value is shown in Table 1.

[0142] S4, take about 3 g of the ground solid 1 and add it to a clean conical flask, add 150 mL of a mixed solvent of pure water and ethanol (the mass ratio of pure water to ethanol is 50:50) to the conical flask, place the conical flask on a heating table, connect the reflux tube and condensed water, and reflux for 5 hours at 80°C.

[0143] S5, use filtration to separate the mixed solution in the conical flask that has completed the reflux in step S4, put the filtered solid 2 (that is, the negative electrode material without CMC or the negative electrode material with CMC removed) into a surface dish with a cover, and place it in a forced air drying oven to dry; take the dried solid 2 and put it into an agate mortar and grind it into powder, and take 10 mg of the ground solid 2 powder for TG testing. The TG test conditions are: N2 atmosphere, heating rate 2k / min, test temperature range 25-750℃. The TG test obtains the weight loss curve of solid 2 (that is, the negative electrode material without CMC or the negative electrode material with CMC removed) Figure 3 As shown, according to the weight loss curve, the weight loss rate of solid 2 (that is, the negative electrode material without CMC or the negative electrode material with CMC removed) is obtained, that is, the second weight loss rate, recorded as D2, and the value is shown in Table 1.

[0144] S6, take 10 mg of each standard substance of pure SBR emulsion, pure CMC dry powder, artificial graphite, and SP respectively, and conduct TG test. The TG test conditions are: N2 atmosphere, heating rate 2k / min, test temperature range 25-750℃, and obtain their respective weight loss curves, such as Figure 4 and Figure 5 As shown. Figure 5 The weight loss curve of the SBR standard substance and the CMC standard substance are obtained, where: the weight loss ratio of the SBR standard substance is also the third weight loss ratio, recorded as D1; ​​the weight loss ratio of the CMC standard substance is also the fourth weight loss ratio, recorded as D3. The weight loss ratio of the artificial graphite standard substance, the weight loss ratio of the SP standard substance, the weight loss ratio of the SBR standard substance and the weight loss ratio of the CMC standard substance are shown in Table 1.

[0145] S7, through TG test, it can be obtained that artificial graphite has no weight loss at 25-750℃ under N2 atmosphere, and the carbon conductive agent SP loses less than 0.4% of its weight at 25-750℃ under N2 atmosphere. In the negative electrode material formula, the proportion of SP is generally less than 3wt%, and the weight loss of SP in the negative electrode material is less than 0.02%, which can be ignored. According to the weight loss ratio of SBR standard substance and solid 2 at 25-750℃, the mass content of water-based binder SBR in the negative electrode material formula is calculated according to formula (1), and according to the weight loss ratio of CMC standard substance, SBR standard substance and solid 1 at 25-750℃, the mass content of water-based dispersant CMC in the negative electrode material formula is calculated according to formula (2), and then the mass content of carbon material (main material artificial graphite and carbon conductive agent SP) is calculated according to formula (3).

[0146] Table 1

[0147]

[0148] The mass content of aqueous binder SBR in the negative electrode material formula = (1.79% / 92.95%)*100% = 1.93%

[0149] The mass content of aqueous dispersant CMC in the negative electrode material formula = [(2.51%-1.93%*92.95%) / 52.76%]*100% = [(2.51%-1.79%) / 52.76%]*100% = 1.36%

[0150] The carbon material (artificial graphite+carbon-based conductive agent SP) in the negative electrode material formula = (1-1.93%-1.36%)*100%=96.71%.

[0151] Example 2

[0152] This embodiment is basically the same as Embodiment 1, except that:

[0153] In step S4, the mixture is refluxed at 60° C. for 6 h.

[0154] In step S5, the weight loss rate D2 of the solid 2 (ie, the negative electrode material without CMC or the negative electrode material with CMC removed) obtained by TG test is 1.82%.

[0155] In step S7:

[0156] The mass content of aqueous binder SBR in the negative electrode material formula = (1.82% / 92.95%)*100% = 1.95%

[0157] The mass content of aqueous dispersant CMC in the negative electrode material formula = [(2.51%-1.95%*92.95%) / 52.76%]*100% = [(2.51%-1.82%) / 52.76%]*100% = 1.31%

[0158] The carbon material (artificial graphite+carbon-based conductive agent SP) in the negative electrode material formula = (1-1.95%-1.31%)*100%=96.74%.

[0159] Example 3

[0160] This embodiment is basically the same as Embodiment 1, except that:

[0161] In step S4, the mixture is refluxed at 90° C. for 4 h.

[0162] In step S5, the weight loss rate D2 of the solid 2 (ie, the negative electrode material without CMC or the negative electrode material with CMC removed) obtained by TG test is 1.75%.

[0163] In step S7:

[0164] The mass content of aqueous binder SBR in the negative electrode material formula = (1.75% / 92.95%)*100% = 1.88%

[0165] The mass content of aqueous dispersant CMC in the negative electrode material formula = [(2.51%-1.88%*92.95%) / 52.76%]*100% = [(2.51%-1.75%) / 52.76%]*100% = 1.44%

[0166] The carbon material (artificial graphite+carbon-based conductive agent SP) in the negative electrode material formula = (1-1.88%-1.44%)*100%=96.68%.

[0167] Example 4

[0168] This embodiment is basically the same as Embodiment 1, except that:

[0169] In step S4, 150 mL of a mixed solvent of pure water and ethylene glycol (the mass ratio of pure water to ethylene glycol is 70:30) is added to a conical flask.

[0170] In step S5, the weight loss rate D2 of the solid 2 (ie, the negative electrode material without CMC or the negative electrode material with CMC removed) obtained by TG test is 1.85%.

[0171] In step S7:

[0172] The mass content of aqueous binder SBR in the negative electrode material formula = (1.85% / 92.95%)*100% = 1.99%

[0173] The mass content of aqueous dispersant CMC in the negative electrode material formula = [(2.51%-1.99%*92.95%) / 52.76%]*100% = [(2.51%-1.85%) / 52.76%]*100% = 1.25%

[0174] The carbon material (artificial graphite+carbon-based conductive agent SP) in the negative electrode material formula = (1-1.99%-1.25%)*100%=96.76%.

[0175] Example 5

[0176] This embodiment is basically the same as Embodiment 1, except that:

[0177] In step S2, 100 mL of ethyl methyl carbonate (EMC) was added to a clean conical flask.

[0178] In step S3, the weight loss rate D4 of the solid 1 (ie, the negative electrode material) obtained by TG testing is 2.58%.

[0179] In step S5, the TG test shows that the weight loss rate D2 of the solid 2 (ie, the negative electrode material without CMC or the negative electrode material with CMC removed) is 1.89%.

[0180] In step S7:

[0181] The mass content of aqueous binder SBR in the negative electrode material formula = (1.89% / 92.95%)*100% = 2.03%

[0182] The mass content of aqueous dispersant CMC in the negative electrode material formula = [(2.58%-2.03%*92.95%) / 52.76%]*100% = [(2.58%-1.89%) / 52.76%]*100% = 1.31%

[0183] The carbon material (artificial graphite+carbon-based conductive agent SP) in the negative electrode material formula = (1-2.03%-1.31%)*100%=96.66%.

[0184] Example 6

[0185] This embodiment is basically the same as Embodiment 1, except that:

[0186] A known negative electrode material formula is: artificial graphite: aqueous dispersant CMC: aqueous binder SBR: carbon-based conductive agent SP = 95.6wt%: 1.4wt%: 2wt%: 1wt%.

[0187] The inventors, knowing the material composition of the negative electrode material but not knowing the specific content of each material composition, used the analysis and detection method of the negative electrode material formula content of this embodiment to analyze and detect the mass content of the aqueous binder SBR, the aqueous dispersant CMC and the carbon material (artificial graphite and the carbon-based conductive agent SP) in the negative electrode material. In the specific test analysis method:

[0188] Not including step S1 and step S2;

[0189] Step S3 is: the known negative electrode material is put into an agate mortar as solid 1 and ground into powder, and 10 mg of the ground solid 1 powder is taken for TG test. The TG test conditions are: N2 atmosphere, heating rate 2k / min, test temperature range 25-750°C. The TG test obtains that the weight loss rate D4 of solid 1 (i.e., negative electrode material) is 2.55%.

[0190] In step S5, the weight loss rate D2 of the solid 2 (ie, the negative electrode material without CMC or the negative electrode material with CMC removed) obtained by TG test is 1.85%.

[0191] In step S7:

[0192] The mass content of aqueous binder SBR in the negative electrode material formula = (1.85% / 92.95%)*100% = 1.90%

[0193] The mass content of aqueous dispersant CMC in the negative electrode material formula = [(2.55%-1.90%*92.95%) / 52.76%]*100% = [(2.55%-1.85%) / 52.76%]*100% = 1.33%

[0194] Carbon material in the negative electrode material formula (artificial graphite + carbon-based conductive agent SP) = (1-1.90%-1.33%) * 100% = 96.77% In this application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0195] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0196] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A method for analyzing and detecting the content of a negative electrode material formula, characterized in that: The negative electrode material is composed of a carbon material, an aqueous binder and an aqueous dispersant, and the carbon material is composed of graphite and a carbon-based conductive agent; the analysis and detection method includes: Taking a portion of the negative electrode material for a first thermogravimetric analysis to obtain a first weight loss rate; removing the aqueous dispersant from the remaining negative electrode material to obtain a negative electrode material free of the aqueous dispersant; Performing a second thermogravimetric analysis on the negative electrode material not containing the aqueous dispersant to obtain a second weight loss rate; The standard substances of the water-based binder and the water-based dispersant are subjected to a third thermogravimetric analysis and a fourth thermogravimetric analysis within the first temperature range to obtain a third weight loss rate and a fourth weight loss rate; within the first temperature range, the graphite does not undergo thermal weight loss, and the weight loss of the carbon-based conductive agent is negligible; The mass content of the aqueous binder in the negative electrode material is calculated according to formula (1), and the mass content of the aqueous dispersant in the negative electrode material is calculated according to formula (2): C1=D2 / D1*100%Formula (1) C2=(D4-D2) / D3*100%Formula (2) Among them, D1 is the third weight loss rate, D2 is the second weight loss rate, D3 is the fourth weight loss rate, D4 ​​is the first weight loss rate, C1 is the mass content of the aqueous binder in the negative electrode material, and C2 is the mass content of the aqueous dispersant in the negative electrode material.

2. The analysis and detection method according to claim 1, characterized in that: The method for analyzing and detecting the content of the negative electrode material formula also includes: The mass content of the carbon material in the negative electrode material is calculated according to the following formula: C3=(1-C1-C2)*100% Wherein, C3 is the mass content of the carbon material in the negative electrode material.

3. The analysis and detection method according to claim 1, characterized in that: The first temperature range is 25-750° C.; and / or, The third thermogravimetric analysis and the fourth thermogravimetric analysis are both performed in an inert gas atmosphere; and / or. The heating rates of the third thermogravimetric analysis and the fourth thermogravimetric analysis are both 1-3 k / min; and / or, The conditions of the first thermogravimetric analysis and the second thermogravimetric analysis are: inert gas atmosphere, heating rate 1-3k / min, and test temperature range 25-750°C.

4. The analysis and detection method according to claim 1, characterized in that: The aqueous dispersant is removed from the remaining negative electrode material to obtain a negative electrode material without the aqueous dispersant, comprising: The remaining negative electrode material is subjected to a first reflux in a first solvent, followed by a first filtration and a first drying to obtain the negative electrode material free of the aqueous dispersant.

5. The analysis and detection method according to claim 4, characterized in that: The first solvent includes water and an organic solvent, and the organic solvent includes at least one of methanol, ethanol, ethylene glycol, and propanol; and / or, The temperature of the first reflux is 60-90° C.; and / or, The first reflux time is 4-6h.

6. The analysis and detection method according to claim 1, characterized in that: The method for analyzing and detecting the negative electrode material formula content further includes a step of first grinding the negative electrode material before performing the first thermogravimetric analysis and the step of removing the aqueous dispersant; and / or, The method for analyzing and detecting the negative electrode material formula content further includes a step of performing a second grinding on the negative electrode material not containing the aqueous dispersant before performing the second thermogravimetric analysis; and / or, The negative electrode material is a fresh negative electrode material mixed with a carbon material, an aqueous binder and an aqueous dispersant, or a negative electrode material obtained from a negative electrode sheet of a lithium-ion battery to be tested.

7. The analysis and detection method according to claim 6, characterized in that: When the negative electrode material is a negative electrode material obtained from a negative electrode plate of a lithium ion battery to be tested, the method for analyzing and detecting the formula content of the negative electrode material further includes: Washing the negative electrode sheet, performing a second drying, and then scraping the negative electrode material layer of the negative electrode sheet, and then performing a second reflux, a second filtration, and a third drying in a second solvent to obtain the negative electrode material; and / or, When the negative electrode material is a negative electrode material obtained from a negative electrode plate of a lithium ion battery to be tested, the method for analyzing and detecting the formula content of the negative electrode material further includes: The lithium-ion battery to be tested is discharged to a cut-off voltage, and then disassembled in an environment with a humidity of less than 10% to obtain the negative electrode sheet.

8. The analysis and detection method according to claim 7, characterized in that: The washing solvent and the second solvent both include at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methanol, ethanol, ethylene glycol, and propanol; and / or, The temperature of the second reflux is 60-90° C.; and / or, The second reflux time is 4-6 hours; and / or, The discharge current of the lithium-ion battery to be tested is 0.01-0.05C.

9. The analysis and detection method according to any one of claims 1 to 8, characterized in that: The graphite includes at least one of artificial graphite, natural graphite, and mesophase carbon microspheres; and / or, The carbon-based conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, porous carbon, graphene, multi-walled carbon nanotubes, and single-walled carbon nanotubes; and / or, The water-based binder includes at least one of styrene butadiene and modified organic emulsions thereof, styrene acrylate and modified organic emulsions thereof, polyethylene emulsions, and polypropylene emulsions; and / or, The aqueous dispersant includes at least one of carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxyethyl cellulose, and lithium carboxyethyl cellulose.

10. Application of the method for analyzing and detecting the content of negative electrode material formula according to any one of claims 1 to 9 in the field of secondary batteries.

Citation Information

Patent Citations

  • Method for detecting content of silicon-based material in silicon-containing negative electrode sheet of lithium ion battery

    CN110702556A

  • Component test analysis method of lithium ion battery positive electrode material

    CN110987711A

  • Method for detecting content of surface coating layer of graphite negative electrode material of lithium battery

    CN113405938A

  • Method for testing component content of battery positive electrode

    CN118624858A

  • Battery positive electrode formula content detection method

    CN118777116A

Cited By

  • New energy cell pole piece core characteristic identification method based on coating technology and application

    CN121299036A

  • New energy cell core feature identification method based on coating technology and application

    CN121299036B